Myth as memory - Camp, Micah Sunshine (Rhodes University, 2026)
This thesis explores the narratives surrounding the iconic Greek heroes Achilles, Odysseus, Heracles, and Theseus, considering the underlying cultural and symbolic meanings that are embedded in these narratives with a specific focus on ethnoastronomical and ethnobotanical folk knowledge, and emphasising how oral traditions transmit cultural beliefs. Through heroic narratives, this thesis considers the aspirational role of heroes and their reflection on societal and moral values and cultural themes that have endured through to modern times. The heroes’ narratives evolved to reflect changing social and political landscapes, representing tensions between innovation and tradition in Greek society. This thesis takes a specific focus on how heroes and their narratives are connected to celestial and botanical symbols and knowledge. It further explores the way these symbols were utilised by the Greeks in conceptualisations of the world around them. These heroes continue to captivate modern audiences, providing reflections of enduring social, moral, philosophical, political, and religious ideas that evolve in response to a societal need. The folklore elements present in hero narratives can, and have, been used to reflect a reclamation of identity and as a propaganda tool. The enduring power of heroic narratives lies not only in their ability to reflect and shape cultural identities but also in their potential use as tools of political influence. They serve as both mirrors and moulds for our own time, presenting and shaping idealised representations of cultural values.
folklore, cosmology, and cultural patterning in selected ancient Greek heroic narratives
Keywords: Folklore; Ethnoastronomy; Mnemonics; Greek literature; History and criticism; Mythography